FAKTOR-FAKTOR YANG MEMPENGARUHI MOBILITAS ULANG-ALIK PENDUDUK DARI DESA OESAO KE KOTA KUPANG KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Wangga, Dionisius; Samin, Mikael; Rahmawati, Arfita (Universitas Nusa Cendana, 2022)
This study aims to: (1) determine the effect of age on traders of agricultural products in Oesao Village to carry out shuttle mobility to Kupang City; (2) find out the effect of Distance on traders of agricultural products in Oesao Village, they carry out shuttle mobility to Kupang City; (3) find out the effect of income level on traders of agricultural products in Oesao Village, they carry out shuttle mobility to Kupang City; (4) determine the effect of land ownership on agricultural product traders, Oesao Village conducts shuttle mobility to Kupang City. This study used quantitative analysis descriptive method with a sample of 47 people. Data sources consist of primary data and secondary data collected by means of questionnaires and documentation. After that, the data processed through the process of editing, coding and tabulation. and analyzed by simple regression analysis method. The results of the analysis in the study show that: (1) the distance variable has no significant effect on the decision to carry out shuttle mobility from Oesao Village to Kupang Village with a significant value of 0.624 > 0.05; (2) The income level variable has a significant effect on the Round-trip Mobility Decision for agricultural product traders from Oesao Village to Kupang City with a significant value of 0.022 <0.05; (3) Age variable has a significant effect on the mobility decision of traders of agricultural products from Oesao Village to Kupang City with a significant value of 0.016 <0.05; (4) The variable of land ownership has a significant effect on the Round-trip Mobility Decision of traders of agricultural products from Oesao Village to Kupang City with a significant value of 0.049.